MEMBANGUN GENERASI LITERAT MASYARAKAT PESISIR PANTAI: GERAKAN LITERASI “TANAH OMBAK” - Yoseva Silaen; Dian Hasfera (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2018)
Literacy is a form of programs and activities that currently exist in developing the culture of reading Indonesian society. This is very much supported by the government, seen from the national literacy program and the enactment of Undang-undang No. 3 of 2017 concerning the Bookkeeping System. The incessant literacy movement is related to the increasing number of literacy activists and the growth of Community Reading Parks (TBM), literacy villages and reading rooms in the community. Tanah Ombak is one of the reading rooms in the fishing village of Purus 3 in the coastal area of Padang. Officially established since the end of 2014 and later notarized in 2015 where Syuhendri was the founder and supported by Yusrizal KW. Tanah Ombak is in a poor and alarming condition of the community, where children are very close to the world of evil and speak harshly. This research uses descriptive method, namely by describing the role of Tanah Ombak for the community, what achievements have been achieved, and what programs will be formulated by Tanah Ombak in increasing literacy activities in the community.